Luminescent Platinum(II) Complexes Containing Cyclometallated Diaryl Ketimine Ligands: Synthesis, Photophysical and Computational Properties - Pandya, SU; Moss, KC; Bryce, MR; Batsanov, AS; Fox, MA; Jankus, V; Al Attar, HA; Monkman, AP (European Journal of Inorganic Chemistry, 2010)
A new series of platinum(II) complexes containing cyclometallated diaryl ketimine ligands has been synthesised. The route involves reaction of diaryl ketimines with K[PtCl3(dmso)] to obtain trans-[PtCl2(imine)(dmso)] species, which underwent cyclometallation upon heating in toluene to give [PtCl{Ar′(ArC=NH)}(dmso)] complexes 12b–17b. N-Hydroxy and N-phenyl analogues 18b and 21 were also synthesised. In complexes 19 and 20 the auxiliary chlorido and dmso ligands were replaced by an acetylacetonato ligand. The photophysical properties of the cyclometallated complexes are reported. The emission bands at λmax ≈ 450 and 550 nm are assigned to mixed-ligand and MLCT states having significant singlet and triplet character, respectively. By varying the structure of the aromatic ligand the efficiency of phosphorescence can be increased to 4.3 % for 15b (Ar′ = 1-naphthyl). Theoretical calculations show that the low-energy transitions in all the cyclometallated systems involve mainly the frontier orbitals, HOMO and LUMO. These are mixed chlorido–metal–ligand to largely π*-C=N transitions. Most of the observed phosphorescence data can be explained by the geometric change on going from the S0 to the T1 states. An organic light-emitting device has been fabricated by using complex 15b as the emissive dopant in a poly(vinylcarbazole) host. Broad electroluminescence spanning the range 500–750 nm was observed.
EPrint Processing Status: Publisher does not permit full text to be deposited
Keywords: Platinum; Complexation; Cyclometallation; Photoluminescence; Density functional calculations; Light-emitting devices.